2022
DOI: 10.7150/ijbs.70172
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 receptor and malignant cancers: Association of CTSL expression with susceptibility to SARS-CoV-2

Abstract: CTSL is expressed by cancerous tissues and encodes a lysosomal cysteine proteinase that regulates cancer progression and SARS-CoV-2 entry. Therefore, it is critical to predict the susceptibility of cancer patients for SARS-CoV-2 and evaluate the correlation between disease outcomes and the expression of CTSL in malignant cancer tissues. In the current study, we analyzed CTSL expression, mutation rate, survival and COVID-19 disease outcomes in cancer and normal tissues, using online databases. We also performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…It was reported that SARS-CoV-2 can directly infect and injure many extrapulmonary organs, like the heart, kidney, liver, pancreas, and gastrointestinal tract 18 20 , usually with high CTSL expression levels. Besides, the mRNA expression level of CTSL is higher than angiotensin-converting enzyme 2 (ACE2), FURIN, and TMPRSS2 in human lung tissues 21 . Recently, we found that in SARS-CoV-2-infected patients, the circulating blood level of CTSL is highly correlated with the severity and course of COVID-19 symptoms.…”
Section: Introductionmentioning
confidence: 98%
“…It was reported that SARS-CoV-2 can directly infect and injure many extrapulmonary organs, like the heart, kidney, liver, pancreas, and gastrointestinal tract 18 20 , usually with high CTSL expression levels. Besides, the mRNA expression level of CTSL is higher than angiotensin-converting enzyme 2 (ACE2), FURIN, and TMPRSS2 in human lung tissues 21 . Recently, we found that in SARS-CoV-2-infected patients, the circulating blood level of CTSL is highly correlated with the severity and course of COVID-19 symptoms.…”
Section: Introductionmentioning
confidence: 98%
“…Cancer patients are considered a high-risk population for contracting severe COVID-19 disease that could lead to death [ 3 ]. Oncologic patients often present co-morbidities and risk factors associated with COVID-19 severity, including older age, chronic inflammation and genetic alterations associated with severe disease [ 2 , 3 , 4 , 5 ]. Patients with cancer are usually immunocompromised by the disease and antineoplastic treatments [ 3 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The following day, membranes were washed three times with TBST (Tris-buffered saline containing 0.1% Tween20) for 15 min each time, and the blots were incubated with an anti-mouse HRP secondary antibody (1:5000 dilution) in 2% fat-free milk for a further 2 h. Subsequently, the membranes were three times as above. The protocol for western blot in breast cancer tissues and its matched healthy tissues from Chinese breast cancer patients was described previously ( 25 , 26 ). All experiments were repeated three times.…”
Section: Methodsmentioning
confidence: 99%